2011
DOI: 10.14238/pi51.4.2011.213-6
|View full text |Cite
|
Sign up to set email alerts
|

School performance in pubertal adolescents with dysmenorrhea

Abstract: Background Dysmenorrhea is a common gynecological symptom reported in adolescent girls. Prevalence of the condition has been reported to be 45 - 75%. Absenteeism from work and school as a result of dysmenorrhea is common (13 - 51% of women have been absent at least once, and 5 - 14% are often absent due to the severity of symptoms).Objective To compare school performance in pubertal adolescent girls with and without dysmenorrhea.Methods This cross-sectional study was conducted in June 2010 in adolescent female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
(20 reference statements)
1
1
0
Order By: Relevance
“…The results showed that students who did not have primary dysmenorrhea had more pass marks than students with dysmenorrhea but was not statistically significant. Our finding was similar to that of Alam et al [24] in Indonesia who found no significant difference in academic performance of students with and without dysmenorrhea though their cut off mark for good and poor average was 7.5/20. We did not find a correlation between pain intensity and performance in contrast to findings from other studies [25] [28] who found a decrease in academic performance with increase dysmenorrhea severity.…”
Section: Attention During Lectures Home Studies and Academicsupporting
confidence: 91%
See 1 more Smart Citation
“…The results showed that students who did not have primary dysmenorrhea had more pass marks than students with dysmenorrhea but was not statistically significant. Our finding was similar to that of Alam et al [24] in Indonesia who found no significant difference in academic performance of students with and without dysmenorrhea though their cut off mark for good and poor average was 7.5/20. We did not find a correlation between pain intensity and performance in contrast to findings from other studies [25] [28] who found a decrease in academic performance with increase dysmenorrhea severity.…”
Section: Attention During Lectures Home Studies and Academicsupporting
confidence: 91%
“…Our respondents being city dwellers like the ones in Yaoundé have figures similar to the latter. However this study date from 1998 but with the shift toward lowering menarcheal age at the rate of 1.1 month per decade [22] [23] [24], it is understandable that our value is slightly lower than theirs. Our value was also similar to results of studies in other countries 12.7 years in Nigeria [25], 13.0 years in Egypt [26], 13.3 years in Indonesia [27].…”
Section: Menstrual Characteristicsmentioning
confidence: 81%